2021
DOI: 10.21203/rs.3.rs-522567/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Farmers’ Adoption of Soil and Water Conservation Practices: the Case of Lege-lafto Watershed, Dessie Zuria District, South Wollo, Ethiopia

Abstract: This study was conducted to assess farmers’ adoption decisions of soil and water conservation practices in Lege-Lafto Watershed, Dessie Zuria District, South Wollo, Ethiopia. Data were collected from 304 farmers using household survey, and through focus group discussions, key informant interviews, and field observation. Binary Logistic regression model and descriptive statistics were used to analyze the data. The results indicated that about 64% of the farmers adopted soil and water conservation practices in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In a similar vein, Sisey (2009) discovered that growing older was linked to more agricultural expertise and experience, which boosted the uptake of SWC policies. Additionally, Fikru (2009) observed that more experienced Sex--The adoption of SWC practices was significantly impacted by the sex of household heads, according to the findings of the binary logistic regression (B = 1.043; P < 0.001). The Wald statistic (3.287) and the Exp (B) = 0.839 support the idea that there was a negative correlation between sex and adoption, meaning that female household heads were less likely than male household heads to adopt SWC practices.…”
Section: And Discussion 1 Factors Affecting Farmer's Adoption Of Soil...mentioning
confidence: 96%
See 4 more Smart Citations
“…In a similar vein, Sisey (2009) discovered that growing older was linked to more agricultural expertise and experience, which boosted the uptake of SWC policies. Additionally, Fikru (2009) observed that more experienced Sex--The adoption of SWC practices was significantly impacted by the sex of household heads, according to the findings of the binary logistic regression (B = 1.043; P < 0.001). The Wald statistic (3.287) and the Exp (B) = 0.839 support the idea that there was a negative correlation between sex and adoption, meaning that female household heads were less likely than male household heads to adopt SWC practices.…”
Section: And Discussion 1 Factors Affecting Farmer's Adoption Of Soil...mentioning
confidence: 96%
“…Kessler (2006), who recommended that farmers participate in more appropriate SWC activities near their homes, supports this outcome. Conversely, Fikru (2009) contended that individuals adopted fewer SWC techniques depending on how far their residence was from their farm. Alemante (2010) discovered no correlation between the distance between farms and the adoption of SWC methods.…”
Section: And Discussion 1 Factors Affecting Farmer's Adoption Of Soil...mentioning
confidence: 99%
See 3 more Smart Citations